Evaluating the efficacy of probiotics and ascorbic acid as anti-stress agents against heat stress in broiler chickens - Sumanu, Victory Osirimade; Naidoo, Vinny; Oosthuizen, Marinda Catharina; Chamunorwa, Joseph Panashe (Frontiers in Veterinary Science, 2024)
Heat stress poses a substantial challenge to poultry production worldwide, highlighting the urgent need for effective management strategies. This study investigated the efficacy of probiotics (Saccharomyces cerevisiae) and ascorbic acid as antistress agents using cloacal and body surface temperatures (CT and BST) as heat stress biomarkers in broiler chickens. A total of 56 broiler chicks were used for the experiment and were divided into four distinct groups: control, probiotics (1 g/kg of feed), ascorbic acid (200 mg/kg of feed) and the combination of probiotics and ascorbic acid (1 g/kg and 200 mg/kg of feed, respectively). The study lasted 35 days; measurements were taken for ambient temperature (AT), CT, and BST. The ambient temperature in the pens consistently exceeded the thermoneutral zone (TNZ) established for broiler chickens. The CT values for broiler chickens in the probiotic group were significantly lower (p < 0.05) compared to the control group. Additionally, the BST values in the probiotic and probiotic + ascorbic acid groups were significantly lower (p < 0.05) than those in the control group. The findings suggest that incorporating probiotics, with or without ascorbic acid, can effectively reduce CT and BST values in broiler chickens thereby, enhancing thermoregulation when compared to the control group. This implies that using probiotics in poultry diets may enhance health and growth performance, potentially leading to better feed efficiency and reduced reliance on antibiotics. Implementing these dietary strategies could improve the productivity and welfare of broiler chickens in commercial settings.